The American thriller - Hoppenstand, Gary (Ipswich, Massachusetts : Salem Press, a division of EBSCO Information Services, Inc. ; Amenia, NY : Grey House Publishing, 2014)
"This volume in the Critical Insights series presents a variety of new essays on the American thriller, a genre in which 'ordinary' heroes are faced with an enemy set on destroying them or something treasured such as freedom or democracy. Rounding out the volume are a list of related thrillers not discussed in the book as well as a bibliography of critical sources for readers seeking to study this theme in greater depth."--Provided by publisher.
About this volume / Gary Hoppenstand -- On the American thriller / Gary Hoppenstand -- Critical contexts. The crime thriller in context / Kate Watson -- The legal thriller in context / Ayoola Onatade -- The techno thriller in context / John A. Dowell -- The psychological thriller in context / Kristopher Mecholsky -- Critical readings. Death's head: Thomas Harris / Abby Bentham -- Lee Child's pure, uncomplicated hero / Elizabeth Blakesley -- Robert Bloch's archetypal thriller: Psycho, the novel / Garyn G. Roberts -- The elusive genius of Michael Crichton / Chris Richardson -- James Patterson: An uncertain legacy / Philip L. Simpson -- John Grisham: The master of the fast-moving legal thriller / Susan J. Tyburski -- In the popular tradition / Helen S. Garson -- The life of Robin Cook / Lorena Laura Stookey.
Includes bibliographical references (pages 193-194) and index.
Keywords: Suspense fiction, American -- History and criticism; Suspense in literature; Suspense fiction, American -- History and criticism